efektivitas terapi finger-hold terhadap perubahan skala nyeri disminore pada remaja putri: pre-experimental - Luh Putu Artika PurnamaDewi; Ni Putu Diwyami; I Made Rai Mahardika (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2026)
Abstract Introduction: Dysmenorrhea is the most common gynecological complaint among adolescent girls and can disrupt daily activities, with a prevalence in Indonesia reaching 64.5% and 74.42% among girls aged 12–16 years, while structured non-pharmacological management among junior high school-aged girls remains limited. Objective: This study aimed to determine the effect of hand finger relaxation using the finger-hold method on reducing dysmenorrhea pain intensity among female students at SMP Negeri 4 Denpasar. Method: A quantitative pre-experimental one-group pretest-posttest design involving 66 grade IX respondents selected through purposive sampling. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after a ±30-minute finger-hold intervention, analyzed using the Wilcoxon Signed Ranks Test. Results: Mean pain intensity before intervention was 6.44 (SD=1.11), mostly moderate pain (60.6%), decreasing to 3.44 (SD=0.81) after intervention with 54.5% in the mild category. Statistical tests showed p=0.000 and Z=−7.147. Conclusion: The finger-hold relaxation technique had a significant effect on reducing dysmenorrhea pain intensity among female students at SMP Negeri 4 Denpasar.